A QUALITATIVE STUDY OF CONSUMER BUYING BEHAVIOR IN RURAL AREA ON DURABLE GOODS AT KANEYAN VILLAGE SOUTH MINAHASA - Warouw, Stacy Nindy; Tielung, Maria V. J. (FEB Universitas Sam Ratulangi Manado, 2016)
Durable goods is a type of goods that meant not to be easily worn, broken or used up and have longer life for example cars, furniture, dishwashers, refrigerators, televisions, DVD players and so on. The main objectives of this study is to learn, observe and found deeper knowledge and information of the buying behavior on consumer in rural area which is in this case the researcher choose Kaneyan village as the object of this study through a qualitative method by having an interview within the 10 informants. The result indicated that there are various obstacle and influence of the consumer in rural area that have different way of buying behavior with the consumer that are not in rural area. It also found a new method of buying that are provided to those consumers in rural area. Through this study, it can tell that the stores who sell durable goods must have a different special way of marketing in order to be able reach the consumer in rural area and even can have a long term relationship with them. The marketers should act in different way to be competitive from other stores, it’s also give different message to the government in that region to create a better way and method for the consumer to be able reach the city easily. Keywords: consumer in rural area, buying behavior, durable goods